2014
DOI: 10.1017/s1751731114000913
|View full text |Cite
|
Sign up to set email alerts
|

Robustness and management adaptability in tropical rangelands: a viability-based assessment under the non-equilibrium paradigm

Abstract: Rangelands provide the main forage resource for livestock in many parts of the world, but maintaining long-term productivity and providing sufficient income for the rancher remains a challenge. One key issue is to maintain the rangeland in conditions where the rancher has the greatest possibility to adapt his/her management choices to a highly fluctuating and uncertain environment. In this study, we address management robustness and adaptability, which increase the resilience of a rangeland. After reviewing ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…In general, the study area seems to follow equilibrium rather than non-equilibrium dynamics (Derry and Boone 2010;von Wehrden et al 2012) as indicated by the relative high precipitation (700 to 1,000 mm/year), the low CV of rainfall (around 20 according to Global map in von Wehrden et al 2012) and the responsiveness to management. Rather than ecological concepts on equilibrium or non-equilibrium dynamics, concepts like risk aversion, diversification, management adaptability, resilience, robustness and sustainability (Accatino et al 2014;Quaas et al 2007;Robinson et al 2015) might be more relevant in these de facto managed systems.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the study area seems to follow equilibrium rather than non-equilibrium dynamics (Derry and Boone 2010;von Wehrden et al 2012) as indicated by the relative high precipitation (700 to 1,000 mm/year), the low CV of rainfall (around 20 according to Global map in von Wehrden et al 2012) and the responsiveness to management. Rather than ecological concepts on equilibrium or non-equilibrium dynamics, concepts like risk aversion, diversification, management adaptability, resilience, robustness and sustainability (Accatino et al 2014;Quaas et al 2007;Robinson et al 2015) might be more relevant in these de facto managed systems.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the response and adaptability of decisions [28,29] to environmental feedback needs to be better reflected. More recent models attempt to address adaptive human behavior to environmental change using agent-based approaches to represent social changes [30][31][32][33].…”
Section: Avoiding Centrism: Integrating Social and Environmental Dimementioning
confidence: 99%
“…However, panarchy may be the most effective in capturing social feedback. Specifically, the subjective versatility of the panarchy approach has been used in many case studies [30,102,103] to examine the effect of social and economic decisions in the system. This is crucial in the management of natural resources; however, more research is needed to advance this approach in consideration of environmental feedbacks upon social dimensions.…”
Section: Avoiding Centrism: Integrating Social and Environmental Dimementioning
confidence: 99%
“…Moving to an upper level of organization would make it relevant to move the focus to a larger temporal scale. This would imply an adjustment of the agro-ecological dynamics considered toward longer term ones such as the grass legume balance like in Kaine and Tozer (2005), the bush encroachment like in Accatino et al (2014) or the underground biomass dynamics like in Joly et al (2014). Widening the temporal scale of the study would make it possible to apply the viability theory to the quantification of the resilience of the system toward extreme events (see Martin, 2004;Deffuant and Gilbert, 2011 for details).…”
Section: Limits and Perspectivesmentioning
confidence: 99%